Investment Governance and Financial Market Integrity: A Policy Evaluation Based on IMF and BIS Reports - Imam Syafi'i; Jenny Yudha Utama; Deo Renaldi Saputra (Capitalis: Journal of Economic Stability, Banking, and Investment, 2026)
This study evaluates the evolution of investment governance and its implications for financial market integrity through a structured policy analysis of International Monetary Fund (IMF) and Bank for International Settlements (BIS) reports issued between 2015 and 2025. Employing a mixed qualitative–quantitative content analysis, the research constructs comparative governance indicators capturing prudential orientation, digital finance regulation, artificial intelligence integration, and sustainability risk supervision. The findings reveal a structural shift in global regulatory discourse from stability-centered post-crisis consolidation toward an integrated framework that incorporates crypto-asset oversight, algorithmic supervision, and climate-related financial risk management. While the IMF prioritizes macro-financial surveillance and systemic resilience, the BIS advances granular supervisory standards and technical implementation mechanisms. The results indicate increasing convergence in strategic objectives alongside differentiated institutional pathways. Financial market integrity emerges as a multidimensional governance outcome shaped by transparency regimes, risk quantification tools, and cross-border coordination. The study contributes a novel comparative index-based evaluation framework and advances theoretical understanding of how global economic governance adapts to technological disruption and sustainability transition pressure.